Research Progress of Photothermal Nanomaterials in Multimodal Tumor Therapy - Shi, Xiaolu; Tian, Ye; Liu, Yang; Xiong, Zhengrong; Zhai, Shaobo; Chu, Shunli; Gao, Fengxiang (Frontiers in Oncology, 2022)
The aggressive growth of cancer cells brings extreme challenges to cancer therapy while triggering the scholars’ exploration to the application of multimodal therapy methods. Multimodal tumor therapy based on photothermal nanomaterials is a new technology to realize tumor cell thermal ablation through near-infrared light irradiation with a specific wavelength, which has the advantages of high efficiency, less adverse reactions, and effective inhibition of tumor metastasis compared with traditional treatment methods such as surgical resection, chemotherapy, and radiotherapy. Photothermal nanomaterials have gained increasing interest due to their potential applications and remarkable properties advantages for tumor therapy. In this review, recent advances and the common applications of photothermal nanomaterials in multimodal tumor therapy are summarized, with a focus on discussing the different types of photothermal nanomaterials and their application in multimodal tumor therapy. Moreover, the challenges and future applications have been prospected.